The Ideal Mother in Media: A Critical Discourse Analysis of Maternal Roles in National News Articles - Addawiatur Rofi'ah Rofi'ah; Luxy Nabela Farez (Journal of Southern Sociological Studies, 2025)
The media play a pivotal role in shaping public understandings of motherhood, particularly in defining what counts as the “ideal mother.” This study explores how Indonesian national media construct maternal discourse, employing Teun A. van Dijk’s Critical Discourse Analysis (CDA) as the primary analytic tool. Three online news/feature articles from Kompas.id, Whiteboard Journal, and Konde.co are examined because they explicitly project distinct images of motherhood. The study also analyses audience reception through comments on the Instagram post @kalis.mardiasih titled “10 ribu di tangan istri yang tepat” (“Ten thousand rupiah in the hands of the right wife”) to observe how the meaning of the “ideal mother” is negotiated in digital spaces. Findings indicate that media portray mothers through inspirational and empathetic narratives, yet subtly normalise sacrifice, moral steadfastness, and domestic responsibility as key metrics of motherhood. Such representations reinforce patriarchal values by personalising women’s structural burdens. In contrast, public comments on social media reveal resistance to perfectionist narratives and call for fairer sharing of family responsibilities. The study concludes that the “ideal mother” discourse is dynamic: it is both reproduced and negotiated in digital arenas and should be shifted toward a paradigm of “good-enough,” equitable, and collectively supported motherhood.